Application of mind mapping combined with the teaching method of problem-based learning in undergraduate teaching of clinical dermatology and venereology - JIANG Shui; YU Bo; WANG Jun; CHEN Guanzhi; DING Kun (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To explore the effect of application of mind mapping combined with the teaching method of problem-based learning (PBL) in undergraduate teaching of clinical dermatology and venereology. Methods This study included a total of 96 undergraduate students who majored in clinical medicine at Qingdao University, and were interns in the dermatology department of the Affiliated Hospital of Qingdao University. The participants were randomly divided into the experimental group (48 cases, using mind mapping combined with the teaching method of PBL) and the control group (48 cases, using traditional PBL teaching method). After the course, the comprehensive evaluation of teaching effect was carried out through written examination and questionnaire survey. Results The written test scores of experimental group were higher than those of the control group (t=3.10, P<0.05). The experimental group was superior to the control group in improving independent learning ability, exercising clinical thinking, integrating course learning, and extending memory duration (P<0.05 for all). Conclusion The mind mapping combined with the teaching method of PBL has better teaching effect than the teaching method of PBL alone in undergraduate teaching of clinical dermatology and venereology.